Cómo se preparan los docentes para actuar en educación propia. Un estudio de casos. (2021)
This article presents a case study of teachers who are trained to teach in an institution of their own education, for a multicultural population with peasant, indigenous Nasa and Afro-descendant members. The objective was to investigate the training of some teachers from an educational institution of their own education to characterize their knowledge and the relationship they establish with those of the indigenous community in which the educational establishment is located. The information was collected through a semi- structured interview implemented with 10 teachers from different areas belonging to an institution of their own education located in the Nasa territory of the department of Cauca, Colombia, which was analyzed through discourse analysis. It is concluded that teacher training programs do not provide sufficient tools to exercise in contexts other than Westernones, however, the teaching experience and the context allow the interweaving of a dialogue of knowledge that enables relevant teaching processes for the model of selfeducation. and that strengthen the knowledge of the Nasa community.